Urgensi Sertifikasi Halal dalam Meningkatkan Pertumbuhan Ekonomi Syariah di Indonesia - Eny Latifah; Yusuf Yusuf (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This study aims to determine the extent of the urgency of halal product certification in increasing Islamic economic growth in Indonesia. The method used is library research. The results of the study show that the urgency of halal certification in the growth of the Islamic economy in Indonesia is: (1) Halal certification is an instrument in the halal chain in the Islamic economy; (2) Halal certification encourages Indonesia's achievements through the implementation of its sharia economic system, and (3) Halal certification plays a role in increasing the quantity of economic growth in Indonesia. The research implication is as a reference and motivation for stakeholders, government and society in accelerating halal certification for target products. The novelty of research is the urgency in the movement for halal certification to move to increase the growth of the Islamic economy in Indonesia.